Nucleation and growth rates of lactose as affected by ultrasound in aqueous solutions - Zamanipoor, M.; Dincer, Tuna; Zisu, B.; Jayasena, Vijay (2013)
The impact of ultrasound on promoting the crystallisation process including an increase in nucleation rate and the formation of more uniform crystals from a large number of substances has been reported in previous studies. This study aimed to investigate the effectiveness of ultrasound in enhancing the crystallisation process of lactose and to model the effects of ultrasonic variables on nucleation rate, growth rate, and size distribution of lactose crystals in aqueous solutions. Ultrasound was applied to the lactose in water solutions at the constant frequency of 20 kHz and at 22 ± 1 °C using an ultrasonic probe. Spectrophotometry and direct microscopy techniques were used to measure the responses under study. The data were analysed by Design Expert software for modelling. The variables that significantly (P < 0.05) affected the responses were lactose concentration and amplitude, with concentration being the most significant. The sonicated sample at the optimal sonication conditions had 10.6 times higher nucleation rate and 5.6 times higher yield as compared to the control. The results of this study emphasised the potential effects of ultrasonic treatment in promoting the nucleation rate and yield in the manufacture of lactose. Furthermore, the fact that sonication time had no significant effect (P > 0.05) on the responses implied that sonication duration can be kept to a minimum to save on energy and costs.